"Why don't behavior analysts do something?" Behavior analysts' historical, present, and potential future actions on sexual and gender minority issues. Issue 1 (11th October 2021) - Capriotti, Matthew R.; Donaldson, Jeanne M.
Abstract : For thousands of years, societies actively practiced the oppression, persecution, and dehumanization of sexual and gender minority (SGM) people (e.g., lesbian, gay, bisexual, transgender, and queer individuals). Rekers and Lovaas' (1974) study is part of that history within behavior analysis. Following requests for retraction, the Society for the Experimental Analysis of Behavior and LeBlanc (2020) issued a formal Expression of Concern about the work. Continued conversation and debate have followed. First, we contextualize debate around retraction of Rekers and Lovaas and the history of behavior analysts' work on SGM issues. Second, we propose 5 steps that leaders in behavior analysis can take with relative immediacy, and we describe 5 research areas that individual behavior analysts could pursue. We conclude that behavior analysts can contribute much toward the liberation of SGM individuals if we begin to bring our science to bear on pressing, socially significant issues facing SGM communities.